2021
DOI: 10.3389/fimmu.2020.611522
|View full text |Cite|
|
Sign up to set email alerts
|

NK Cell Subsets Changes in Partial Remission and Early Stages of Pediatric Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a chronic metabolic disease characterized by the autoimmune destruction of β-cells in the pancreatic islets. T1D is preceded by islet-specific inflammation led by several immune cells. Among them, natural killer (NK) cells are emerging as important players in T1D development. Human NK cells are characterized by CD56 and CD16 expression, which allows classifying NK cells into four subsets: 1) CD56dimCD16+ or effector NK cells (NKeff); 2) CD56brightCD16− or regulatory NK cells (NKreg); 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
(86 reference statements)
4
13
0
Order By: Relevance
“…Furthermore, mechanisms of immune regulation are non-linear along the natural history of T1D—matching well with the proposed relapsing-remitting character of the disease course—and the PR phase is associated with these immunomodulatory changes ( 15 , 16 ). Consistent with this idea, studies investigating changes in immune parameters have reported that patients with the highest frequency of CD4 + CD25 + CD127 hi lymphocytes at disease onset experience the longest PR ( 17 , 18 ), that increased levels of regulatory T, B, and NK cells can be found during T1D progression (which could reflect attempts at restoring self-tolerance) ( 19 , 20 ), and that the absence of IL-4, TNF-α, IL-10, and IL-13 in sera correlates with the length of the remission period ( 21 ). Interestingly, peripheral antigen-specific regulatory T cells (T REG ) diminish during the honeymoon phase in comparison to the time of diagnosis ( 22 ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, mechanisms of immune regulation are non-linear along the natural history of T1D—matching well with the proposed relapsing-remitting character of the disease course—and the PR phase is associated with these immunomodulatory changes ( 15 , 16 ). Consistent with this idea, studies investigating changes in immune parameters have reported that patients with the highest frequency of CD4 + CD25 + CD127 hi lymphocytes at disease onset experience the longest PR ( 17 , 18 ), that increased levels of regulatory T, B, and NK cells can be found during T1D progression (which could reflect attempts at restoring self-tolerance) ( 19 , 20 ), and that the absence of IL-4, TNF-α, IL-10, and IL-13 in sera correlates with the length of the remission period ( 21 ). Interestingly, peripheral antigen-specific regulatory T cells (T REG ) diminish during the honeymoon phase in comparison to the time of diagnosis ( 22 ).…”
Section: Introductionmentioning
confidence: 85%
“…Blood samples from patients with T1D were acquired for centralized measurement of HbA1c, fasting basal and stimulated C-peptide, genetics, and immunology; and insulin requirements were recorded. At the time of T1D diagnosis, HLA typing of DRB1 alleles and islet autoantibodies to IA-2, GAD65, and ZnT8 were determined as previously reported ( 20 ). HbA1c was determined by high-performance liquid chromatography (ADAMS A1c HA-8180V, Arkray, MN, USA) in all patients at each time-point.…”
Section: Methodsmentioning
confidence: 99%
“…Other variations observed during the treatment included the reduction of cells commonly associated with cytotoxic activity such as DN NKT cells and CD56+CD16+ NK cell subsets. However, it is difficult to assure whether the decline was a result of the treatment, as variations in cytotoxic NK cell subsets might also be related to dynamic changes during the disease ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple sclerosis, genetic risk loci have been found to be more enriched in open chromatin regions of NK cells ( 58 ). For type 1 diabetes, it was reported that specific peripheral NK cell subsets may serve as potential candidate biomarkers of disease progression ( 59 ). In the context of CeD, Type 1 innate lymphoid cells, which share a similar cytotoxic profile and several markers with conventional NK cells, have been demonstrated to be altered in active CeD ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%